Learn more about

Refine search

Results (displaying matches 1-50 of 131) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
363.a.43923.1 363.a \(y^2 + x^2y = 11x^5 - 13x^4 - 7x^3 + 10x^2 + x - 2\) $G_{3,3}$ 0
389.a.389.1 389.a \(y^2 + (x^3 + x)y = x^5 - 2x^4 - 8x^3 + 16x + 7\) $\mathrm{USp}(4)$ 0
389.a.389.2 389.a \(y^2 + (x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 0
394.a.394.1 394.a \(y^2 + (x^3 + x)y = 2x^5 + x^4 - 12x^3 + 17x - 9\) $\mathrm{USp}(4)$ 0
523.a.523.1 523.a \(y^2 + (x + 1)y = x^5 - x^4 - x^3\) $\mathrm{USp}(4)$ 0
576.a.576.1 576.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x\) $E_2$ 0
603.a.603.1 603.a \(y^2 + (x^2 + 1)y = x^5 + 8x^4 + 4x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
603.a.603.2 603.a \(y^2 + (x^2 + 1)y = x^5 - x^3 + x\) $\mathrm{USp}(4)$ 0
644.b.14812.1 644.b \(y^2 + (x^3 + 1)y = x^5 - x^4 - 4x^3 + 5x^2 - x - 1\) $\mathrm{USp}(4)$ 0
688.a.704512.2 688.a \(y^2 = 2x^5 - 7x^4 - 8x^3 + 2x^2 + 4x + 1\) $\mathrm{USp}(4)$ 0
688.a.704512.1 688.a \(y^2 = 2x^5 + 4x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
708.a.2832.1 708.a \(y^2 + (x^2 + x + 1)y = x^5\) $\mathrm{USp}(4)$ 0
708.a.19116.1 708.a \(y^2 + (x^3 + 1)y = -x^5 + 4x^2 + 4x - 1\) $\mathrm{USp}(4)$ 0
726.a.1452.1 726.a \(y^2 + (x^2 + 1)y = 2x^5 + 2x^4 + 6x^3 - 2x^2 - x\) $G_{3,3}$ 0
731.a.12427.1 731.a \(y^2 + (x^3 + x^2)y = x^5 + 2x^4 - x - 3\) $\mathrm{USp}(4)$ 0
763.a.763.1 763.a \(y^2 + (x^3 + x)y = -2x^4 + 2x^2 - x\) $\mathrm{USp}(4)$ 0
847.b.9317.1 847.b \(y^2 + (x^2 + 1)y = x^5 + 2x^4 - 3x^3 + 2x^2 - x\) $G_{3,3}$ 0
970.a.1940.1 970.a \(y^2 + (x + 1)y = x^5 + x^4 + x^3 + x^2\) $\mathrm{USp}(4)$ 0
1047.a.3141.1 1047.a \(y^2 + (x^3 + x)y = x\) $\mathrm{USp}(4)$ 0
1104.a.17664.1 1104.a \(y^2 = x^5 - 2x^4 + 4x^3 - 4x^2 + 3x - 1\) $\mathrm{USp}(4)$ 0
1142.a.2284.1 1142.a \(y^2 + (x^3 + x^2)y = -x^4 - x^3 + x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1148.a.8036.1 1148.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 6x^3 + x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
1148.a.47068.1 1148.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ 0
1197.a.10773.1 1197.a \(y^2 + (x^3 + x^2)y = -x^3 - x^2 - x + 2\) $\mathrm{USp}(4)$ 0
1197.a.410571.1 1197.a \(y^2 + (x^2 + 1)y = x^5 + 12x^4 - 7x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 0
1258.a.21386.1 1258.a \(y^2 + xy = x^5 + 4x^4 - 5x^3 - 4x^2 + 5x - 1\) $\mathrm{USp}(4)$ 0
1269.b.102789.1 1269.b \(y^2 + (x^3 + x)y = -2x^6 - x^5 - 21x^4 - 8x^3 - 80x^2 - 16x - 103\) $\mathrm{USp}(4)$ 0
1269.b.102789.2 1269.b \(y^2 + xy = x^5 - x^4 + x^2 + x\) $\mathrm{USp}(4)$ 0
1284.a.5136.1 1284.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 0
1333.a.41323.1 1333.a \(y^2 + (x^2 + 1)y = x^5 - 2x^3 + 3x^2 + 2x\) $\mathrm{USp}(4)$ 0
1345.a.6725.1 1345.a \(y^2 + (x^2 + 1)y = x^5 + x^3 - x\) $\mathrm{USp}(4)$ 0
1462.a.11696.1 1462.a \(y^2 + (x^3 + x)y = 2x^5 - 27x^3 - 38x^2 + 94x + 148\) $\mathrm{USp}(4)$ 0
1611.a.14499.1 1611.a \(y^2 + (x + 1)y = 3x^5 - 8x^4 - 6x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1660.a.6640.1 1660.a \(y^2 + (x^3 + 1)y = x^5 - 4x^3 - 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1708.a.47824.1 1708.a \(y^2 + (x^2 + x + 1)y = -7x^5 + 8x^4 - 3x^3 + x\) $\mathrm{USp}(4)$ 0
1718.a.3436.1 1718.a \(y^2 + (x + 1)y = x^5 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
1776.a.7104.1 1776.a \(y^2 + x^3y = x^5 + 4x^4 + 8x^3 + 15x^2 + 14x + 12\) $\mathrm{USp}(4)$ 0
1872.b.29952.1 1872.b \(y^2 = x^5 - x^4 + 2x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 0
1872.b.479232.1 1872.b \(y^2 + y = 4x^5 - 15x^4 - 8x^3 + 3x^2 + 2x\) $\mathrm{USp}(4)$ 0
2056.c.8224.1 2056.c \(y^2 + (x + 1)y = 2x^5 - 15x^4 + 19x^3 + 3x^2 - 3x\) $\mathrm{USp}(4)$ 0
2102.b.67264.1 2102.b \(y^2 + xy = x^5 + 4x^4 + x^3 - 14x^2 + 8x\) $\mathrm{USp}(4)$ 0
2480.a.39680.1 2480.a \(y^2 = x^5 + 8x^4 - 16x^2 - 13x - 3\) $\mathrm{USp}(4)$ 0
2488.a.9952.1 2488.a \(y^2 + (x + 1)y = 2x^5 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
2496.a.29952.1 2496.a \(y^2 + (x + 1)y = -x^6 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
2676.a.72252.1 2676.a \(y^2 + (x^2 + x + 1)y = 9x^5 - 10x^3 - x^2 + x\) $\mathrm{USp}(4)$ 0
2736.a.10944.1 2736.a \(y^2 + y = 2x^5 - 3x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 0
3222.a.6444.1 3222.a \(y^2 + xy = x^5 - x^4 - 4x^3 + 6x^2 - 2x\) $\mathrm{USp}(4)$ 0
3434.a.6868.1 3434.a \(y^2 + (x^3 + x^2)y = -4x^4 - 6x^3 + 16x^2 + 17x - 12\) $\mathrm{USp}(4)$ 0
3776.a.15104.1 3776.a \(y^2 + (x^2 + 1)y = 2x^5 - 6x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
3792.b.15168.1 3792.b \(y^2 + (x^3 + x)y = -3x^4 - x^3 + 6x^2 + 3x - 3\) $\mathrm{USp}(4)$ 0
Next

Download all search results for